TIKTOK AS A SOCIAL MEDIA INFLUENCE ON LANGUAGE CHANGE AMONG STUDENTS OF ITEBIS PGRI DEWANTARA JOMBANG - Alisa Wardhana; Muhammad Saibani Wiyanto; Suparti (LPPM Universitas PGRI Jombang, 2025)
The way university students use language is changing rapidly due to TikTok. This study aims to address that issue by looking at how students incorporate TikTok phrases into their in-person conversations as part of a larger shift in language. The research included four female college students from ITEBIS PGRI Dewantara Jombang, selected using purposive sampling. Information was collected through semi-structured interviews and analyzed qualitatively. The findings indicate that students frequently and unknowingly use phrases such as damn, pick me, red flag, healing, and cringe in their everyday conversations. These expressions go beyond online platforms, serving as means to convey humor, sarcasm, emotions, and social connections. Their usage reveals an unconscious adaptation, signifying identity and belonging within a community. The results show that the way these terms are used flexibly often points to a continuous change in spoken language influenced by interactions with peers and current trends. Therefore, TikTok serves not just as a source of entertainment but also as a driving force for informal language innovation, bringing in new phrases and promoting language evolution from the ground up within student groups.